Media pembelajaran audio visual pada mata pelajaran SKI di kelas IV MI Al-Ma’arif 02 Singosari - Kanitatun, St (Maliki Interdisciplinary Journal, 2024)
With the development of technology and information, learning media plays an important role in assisting the teaching and learning process, so that an educator can take advantage of learning media which is starting to develop to be used as a tool in conveying material so that the teaching and learning process is easier. The use of audio-visual based learning media is very much needed in the current era. Teachers can see the conditions or characteristics of students and adjust the use of learning media during the teaching and learning process. Likewise with class IV students at MI Al-Ma'arif 02 Singosari, they have adequate facilities so it would be a shame if they didn't use them to create and apply new learning media for them, so that their learning experience is also more varied. The creation and application of audio-visual learning media in SKI lessons has stages that must be gone through, namely analysis first, then there is planning or designing of learning media, after that implementation or trial and evaluation. This is done so that the learning media can be developed and improved for subsequent learning and become notes and insights for teachers and schools.